Fenomena Jilboobs di Kalangan Remaja: Studi Pemaknaan Hijab dalam Perspektif Tafsir Modern - Moh. Husaeni; Abd. Muid N; Muh. Adlan Nawawi (Politeknik Kampar, 2023)
Along with the development of the fashion world of the country, especially the fashion of Muslim women, the model of wearing jilbabpun turned into a fashionable hijab. Starting from this fashionable hijab jilboobs phenomenon arose around 2014 which was discussed on social media, such as facebook and twitter until today is still a trend in hijab. The purpose of this study was to determine the impact of the rise of the phenomenon of jilboobs among adolescents. This type of research is included in the type of library research, characterized by focusing the source of the object of study on library data, both primary and secondary sources. The results of the study that the hijab is something that serves to protect and maintain the honor of women. Based on surah Al-Ahzab/33. 59 and surah an-Nur/24: 31. This verse is related to the custom of arab women during the time of the Qur'an, namely the lack of attention to modesty/fairness in dress/ behavior. The concept of hijab is a concept that regulates biological functions and partnership relationships between men and women associated with dress and ethics. This study has implications for young Muslim women and prospective mufassir in the future in order to continue to explore the scientific field, especially the field of interpretation that speaks of hijab issues while maintaining gender boundaries, promoting the benefit of the Ummah, without forgetting the text, context and contextualization of reality and the development of historical traditions.